Foam Rolling on Uric Acid Levels Profile in Delayed Onset Muscle Soreness (DOMS) post 10 Km Long-Distance Running in Healthy Trained Young Men - Ali, Mohammad Arif; Sadhali, Muchamad; Rahayu, Setya; Anggita, Gustiana Mega; Kurniawati, Dewi Marfu'ah; Mohamed, Ani Mazlina Dewi (ACPES (ASEAN Council of Physical Education and Sport) in cooperation with Universitas Negeri Semarang (UNNES), 2021)
Long distance running (LDR) is an exercise that has a relatively heavy load which can cause Delayed Onset Muscle Soreness (DOMS) and increase Reactive Oxygen Species (ROS) levels. Xanthine, one derivate of ROS will increase 10 times during aerobic activity which is metabolized to Uric Acid (mg/dL) (UA). Foam rolling (FR) is used for the recovery process. This study aims to determine the effect of long distance running on changes in UA levels and the effect of FR as an active recovery against changes in UA levels. This was a quasi-experiment study using a purposive sampling design, one-group repeated measure design of a sample population of young healthy males (17-25 years). The sample consisted of 10 trained young males in Semarang. The average value of UA before intervention was 4.43 mg/dL ± 0.51. In 90 minutes, it was 5.90 mg/dL ± 0.52, in 120 minutes was 5.71 mg/dL ± 0.72 and at 24 hours after intervention was 6.1 mg/dL ± 0.57. LDR has been shown to increase UA levels. FR which is done only once has not been able to reduce UA levels. The percentage of occurrence of post-LDR DOMS occurred at 24 hours.